2010
DOI: 10.1504/ijbge.2010.029556
|View full text |Cite
|
Sign up to set email alerts
|

Curbing the use of Hawala for money laundering and terrorist financing: global regulatory response and future challenges

Abstract: The objective of this paper is to examine the role of Hawala as an Informal Value Transfer System (IVTS) used for money laundering and terrorist financing activities. The paper will provide a background to Hawala as a form of IVTS and highlight the state of global regulatory response to curbing the illicit use of this otherwise benign form of IVTS. The paper will argue for a market mechanism based solution rather than control through regulatory regimes. infrastructure; remittances and regulation of informal va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…This consolidatory behaviour exhibited by the Hawaladars is indicative of a desire to preserve collective reputation of the Hawala system (Humphrey & Schmitz, 1996). The offender, if caught, had to face the Hawala jury who then decide on the appropriate course of corrective action or punishment (Farooqi, 2010). A point worth highlighted is that according to the interviewed respondents, and based on the key findings of this study, there were no reported acts of financial misconduct impressing the high level of trust and confidence that exists within HNets.…”
Section: Materials Arrangements Of Hnets: Building and Consolidating Tmentioning
confidence: 84%
See 1 more Smart Citation
“…This consolidatory behaviour exhibited by the Hawaladars is indicative of a desire to preserve collective reputation of the Hawala system (Humphrey & Schmitz, 1996). The offender, if caught, had to face the Hawala jury who then decide on the appropriate course of corrective action or punishment (Farooqi, 2010). A point worth highlighted is that according to the interviewed respondents, and based on the key findings of this study, there were no reported acts of financial misconduct impressing the high level of trust and confidence that exists within HNets.…”
Section: Materials Arrangements Of Hnets: Building and Consolidating Tmentioning
confidence: 84%
“…There have been cases (even though quite rare) where illegal businesses and criminal activity have been known to be funded through Hawala transfers (Passas, 1999). The minimal transaction record with no legal coverage has resulted in fraud (very few cases) due to the untraceable nature of the Hawala tranfers (Schramm & Taube, 2002;Farooqi, 2010). Additionally, the speed of Hawala transaction completion (in most cases) is faster than fromal channel transfers.…”
Section: Hnets In the Gulf Cooperation Council (Gcc) Regionmentioning
confidence: 99%
“…In HN, carefully controlled and cautiously constituted relationship development, laced with verifications, checks and monitoring, was indicative of an exchange examination regime that was meticulous and elaborate. A fundamental reason for this watchful path to association augmentation was high-risk stature of HN (Farooqi, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This includes no reporting processes, absence of formal documentation and lack of transparency (Ali, 2017). All this is achieved in the absence of a conventional structure where there are no signed contracts or legally agreed set of conditions (Farooqi, 2010). HN work efficiently in dispensing their services.…”
Section: Introductionmentioning
confidence: 99%
“…Underground banking, often known as illegal Hawala service, is a type of informal banking that allows money to be transferred locally and internationally without the use of formal/legitimate financial institutions. As a cheap, fast and reliable money transfer system, they are primarily used by overseas migrant workers for sending remittances to their families in their home countries (Farooqi, 2009).…”
Section: Underground/illicit Banking Activitiesmentioning
confidence: 99%